Full-scale experimental investigation of the fracture behaviours of welding joints of APL X80 wide plate based on DIC technology. (January 2022) - Yang, Yue; Liu, Xiaoben; Wu, Kai; Sui, Yongli; Feng, Qingshan; Wang, Dongying; Zhang, Hong
Highlights: Two wide plate tensile tests were performed on a Ø1422 mm × 25.7 mm X80 pipeline with original and repaired welding joints. Strain gauges and a digital image correlation (DIC) system were used for synchronous monitoring and comparative analysis. The strain capacity of welded joints under different crack mouth opening displacement was analyzed systematically. The difference in bearing capacity between the original and the repaired welding joints was further studied. Abstract: With the advances in material research and pipe manufacturing, the construction of oil and gas pipelines is developing continuously, and the evaluation of welding joints with defects has become the focus of pipeline safety research. In this study, two full-scale wide plate tensile tests were performed on Ø1422 mm × 25.7 mm X80 specimens with original and repaired welding joints. By comparing and analysing the experimental load–displacement responses, as well as the synchronous monitoring results of strain gauge and digital image correlation (DIC) system, the variation trend of the crack mouth opening displacement (CMOD) with distal strain, and the strain capacity of welding joints under different critical CMOD conditions were obtained. This way, the difference in bearing capacity between the original and the repaired welding joints was further determined. Under the same load condition, the driving force of the defect crack expansion at the repaired welding joint was smaller. When the critical CMOD was 0.5 mm and 1.0 mm, the strain capacity of the repaired welding joint was increased by 0.12% and 0.35%, respectively. Therefore, the repair operations of the welding joint effectively strengthen its deformation capacity. This research can provide a valuable data basis for the subsequent verification of numerical analysis models, and can also be referenced for the safety evaluation of pipelines with crack defects.